Fatores determinantes da infecção do sítio cirúrgico em pacientes submetidos a cirurgias de revascularização do miocárdio e implantes de válvulas cardíacas - Nelma de Jesus Braz (2017)
Cardiac surgeries are among the most performed in the world, they are complex with high risk for Surgical Site Infection (SSI), which increases patients' morbi-mortality, prolong hospitalization time and generate additional costs. The objective of this study was to determine the SSI-related factors in patients who underwent myocardial revascularization surgeries (MRS) and heart valve implants. This was a retrospective study, carried out in a hospital in Belo Horizonte, Minas Gerais, after approval by the Research Ethics Committee, under the Report - CAAE-53843316.4.0000.5149. Data related to socio-demographic aspects, comorbidities, predisposing factors of pre, trans and postoperative and occurrence of SSI were collected from records in patients' charts for surgeries performed between the years 2011 and 2015, through a structured instrument. The SSI diagnosis followed criteria defined by the National Healthcare Surveillance Network from Centers for Disease Control. The analyzes were performed in R-softwares version 2.7.1 and EpiInfo version 6.04, using descriptive statistics and measures of central tendency and test with Yates correction, Chi-Square, Fisher's exact, Mann-Whitney and t-student considering Significant p <0.5. The population was composed of 280 adult patients whose mean age was 58 years, range between 19 and 86 years and Standard Deviation of 13.7 years. The comorbidities present among the patients who underwent VCT were hypertension (24.2%) and dyslipidemia (18.3%), in patients with valvular prosthesis implantation, rheumatic fever (19.6%) and hypertension (17.1%), and those of both surgeries, hypertension (23.3%) and dyslipidemia (14%). A total of 52 (18.6%) cases of SSI were found, of which 34 (65.4%) were superficial, 6 (11.5%) were deep incisional and 12 (23.1%) were organ and cavity. The diagnosis of infection occurred during hospitalization in 32 (61.5%) cases and in 20 (38.5%) after hospital discharge. Age was significantly associated with SSI (p = 0.011). The ASA score> 3 (p = 0.012), the EuroSCORE II (p = 0.026), the prophylactic antibiotic up to one hour before the incision (P = 0.005), the time of postoperative hospitalization in both ICU and institution (p <0.001) and total hospital stay (p <0.001) were statistically significant. Approximately 95% of the patients received the ASA 3 and 4 classifications, which characterize patients with severe systemic disease with compromised and life threatening vital functions, respectively. This finding was consonant with the profile of comorbidities requiring a longer hospital stay prior to surgery in hospital as well as in intensive care unit. Attention was also drawn to the impact of SSI in prolonging hospital stay, with the observation that patients without SSI had an average stay of 18.1 days and those with SSI of 33.9 days, which has a direct relation with cost increase with Treatment and risk of morbidity and mortality, as well as other complications. Despite the limitations in the present study, it contributes to a greater attention to the surveillance of the determinants involved in surgical site infections, to the profile of patients and the relevance of cardiac surgical procedures